Microstructure and Thermomechanical Characterization of Fe-28Mn-6Si-5Cr Shape Memory Alloy - Antonio Collazo; Raúl Figueroa; Carmen Mariño-Martínez; Carmen Pérez (Metals, 2021)
Iron-based shape memory alloys (SMAs) have been widely studied during the last years, producing new formulations with potential applications in civil engineering. In the present paper, the microstructure and the thermomechanical behavior of the Fe-28Mn-6Si-5Cr memory alloy has been investigated. At room temperature, the presence of ε-martensite and γ-austenite was confirmed using optical and electron microscopy techniques. The martensitic transformation temperatures (As, Af, Ms, and Mf) were determined by differential scanning calorimetry, together with an X-ray diffraction technique. The use of these techniques also confirmed that this transformation is not totally reversible, depending on the strain degree and the number of thermal cycles. From the kinetics study of the ε → γ transformation, the isoconversion curves (transformation degree versus time) were built, which provided the information required to optimize the thermal activation cycle. Tensile tests were performed to characterize the mechanical properties of the studied alloy. These kinds of tests were also performed to assess the shape memory effect, getting a recovery stress of 140 MPa, after a 7.6% pre-strain and a thermal activation up to 160 °C.